Understanding the ecological context of mental, emotional, and behavioral health problems: A person‐centered approach. Issue 4 (17th January 2019) - Logan‐Greene, Patricia; Linn, Brad; Hartinger‐Saunders, Robin; Nochajski, Thomas; Wieczorek, William F.; Rittner, Barbara
Abstract: Aims: The social/environmental context of youth is important for mental, emotional, and behavioral (MEB) health. This study used person‐oriented methods to examine the influences of family, neighborhood, and poverty on late adolescent MEB outcomes. Methods: Latent class analysis was used to discern significant clusters of at‐risk, diverse young men (N = 625) based on contextual factors; differences in MEB outcomes were examined. Results: Four classes emerged. Resourced and Protected youth had low risk across all indicators. Non‐resourced and Protected youth lived in poverty, poor neighborhoods, but had good parenting; despite low delinquency, substance use was elevated. Resourced but High Risk youth had negative parenting but good neighborhoods. Outcomes included elevated delinquency and mental health problems. Non‐resourced and High Risk youth were poor, lived in bad neighborhoods, and experienced abusive parenting; MEB outcomes were poor. Conclusion: Findings confirm the unique effects that negative parenting, neighborhoods, and poverty have on adolescent development. Implications are discussed.